Shipwrecked identities : navigating race on Nicaragua's Mosquito Coast - Pineda, Baron L., 1967- (Free online access: Knowledge Unlatched., 2006)
Global identity politics rest heavily on notions of ethnicity and authenticity, especially in contexts where indigenous identity becomes a basis for claims of social and economic justice. In contemporary Latin America there is a resurgence of indigenous claims for cultural and political autonomy and for the benefits of economic development. Yet these identities have often been taken for granted. In this historical ethnography, Baron L. Pineda traces the history of the port town of Bilwi, now known officially as Puerto Cabezas, on the Atlantic coast of Nicaragua to explore the development, transformation, and function of racial categories in this region over time. From the English colonial period, through the Sandanista conflict of the 1980s, to the aftermath of the Contra War, Pineda shows how powerful outside actors, as well as Nicaraguans, have made efforts to influence notions about African and Black identity among the Miskito Indians, Afro-Nicaraguan Creole, and Mestizos in the region. In the process, he provides insight into the causes and meaning of social movements and political turmoil.; "Shipwrecked Identities" also includes important critical analysis of the role of anthropologists and other North American scholars in the Contra-Sandinista conflict, as well as the ways these scholars have defined ethnic identities in Latin America. As the indigenous people of the Mosquito Coast continue to negotiate the effects of a long history of contested ethnic and racial identity, this book takes an important step in questioning the origins, legitimacy, and consequences of such claims.